2022
DOI: 10.1039/d2py00600f
|View full text |Cite
|
Sign up to set email alerts
|

Fully biobased triblock copolymers generated using an unconventional oscillatory plug flow reactor

Abstract: Producing block polymers in continuous flow offers significant advantages in terms of versatility, efficiency and scalability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
9
0
2
Order By: Relevance
“…According to a recent study, hydroxyl-diene structures can be used to initiator lactide also in a flow process, offering promise for upscaling. 38 By varying the end-functionalization reagent, a wide range of other architectures besides super-H structures is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, hydroxyl-diene structures can be used to initiator lactide also in a flow process, offering promise for upscaling. 38 By varying the end-functionalization reagent, a wide range of other architectures besides super-H structures is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Pitet et al. recently demonstrated that lactide polymerization onto PFar macroinitiators is also suitable for flow synthesis, highlighting the potential for scale‐up [23] …”
Section: Methodsmentioning
confidence: 99%
“…Pitet et al recently demonstrated that lactide polymerization onto PFar macroinitiators is also suitable for flow synthesis, highlighting the potential for scale-up. [23] The successful preparation of the active initiator species derived from the reaction of DIB/tert-BuLi was tracked by 1 H NMR spectroscopy. Full conversion of the respective benzylic double bonds was observed within the first monitored time frame (< 1 min) (Figure S1).…”
mentioning
confidence: 99%
“…Pitet et al. haben kürzlich gezeigt, dass die Lactid Polymerisation mittels PFar‐Makroinitiatoren auch zur Anwendung in der kontinuierlichen Durchflusssynthese geeignet ist, was das Scale‐Up Potenzial unterstreicht [23] …”
Section: Methodsunclassified
“…Pitet et al haben kürzlich gezeigt, dass die Lactid Polymerisation mittels PFar-Makroinitiatoren auch zur Anwendung in der kontinuierlichen Durchflusssynthese geeignet ist, was das Scale-Up Potenzial unterstreicht. [23] Die Herstellung der aktiven Initiator-Spezies aus der Reaktion von DIB/tert-BuLi wurde mittels 1 Proben…”
unclassified